Service Quality, Customers' Satisfaction and the Moderating Effects of Gender: A Study of Arabic Restaurants. (15th June 2016) - Omar, Muhamad Saufiyudin; Ariffin, Hashim Fadzil; Ahmad, Rozila
Abstract: In the highly competitive business environment, customers' evaluation of service quality is critical for service firms' survival. While there are numerous studies on service quality, very few have investigated the moderating effect of gender on the relationship between service quality and customers' satisfaction in Arabic restaurants. Therefore, this study aims to provide additional insight into the relationship between service quality and customer satisfaction by examining the moderating effect of customers' gender in Arabic restaurants and to identify the extent of each service quality attributes in relation with customer satisfaction as they are perceived by Malaysian customers. A quantitative study was conducted and a set of questionnaire examining the attributes of service quality and customer satisfaction was developed. The data was collected through the survey completed by 411 respondents. Correlation analysis and hierarchical regressions were employed to analyse the data. The correlation analysis shows that all the five service quality attributes – tangibles, reliability, responsiveness, assurance and empathy have positive relationship with customer satisfaction. However, hierarchical regressions indicated a slightly different result. The attributes-tangibles, assurance and empathy are found to have significant relationship with customer satisfaction, but the relationship with the other two attributes – reliability and responsiveness is insignificant. Empathy has a strong positive correlation with customers' satisfaction while responsiveness has a weak positive relation with customers' satisfaction. These findings indicate that restaurant operators should improve their service quality, especially in terms of their responsiveness in order to enhance customers' satisfaction. In addition, gender plays a significant effect in the relationship between service quality and customer satisfaction.